Pengembangan Validitas dan Reliabilitas Instrumen Evaluasi Non Tes Menggunakan Media SPSS di SD Sepang Raya - Aryanty Putri Firdaus; Rosita; Dea Puspa Trianita (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2022)
Abstract ____________________________________________________This study aims to determine the interest in learning students of SD Negeri Sepang Raya Kota Serang. is carried out by providing measuring instruments to the research subjects to be filled in completely. The problem of measuring instruments used when carrying out evaluation activities is often faced with problems of accuracy, consistency and stability so that the measurement results obtained can be measured accurately. This instrument must indeed have accuracy when used. Then the analysis of the question items is carried out to obtain empirical evidence regarding the validity and reliability of measuring instruments. The type of Reliability test used is Cronbach Alpha. The method used in the study is descriptive quantitative, to determine the quality of items from the content of non-test questions measuring students' learning interest using a likert scale. as for the technique of random sampling. Validity test is a test used to test the accuracy of a measuring instrument in measuring something that should be measured. Reliability, or reliability, is the consistency of a set of measurements or a set of measuring instruments. This could be a measurement of the same measuring instrument (a test with a retest) will give the same result, or for a more subjective measurement, whether two assessors give similar scores (reliability between assessors). then the results of after conducting a validity test on the non-test, there are 11 items of question items that are declared valid. Then a reliability test was also carried out on 11 questions of the item. Of the 11 question items, elimination was carried out on one of the questions whose total correlation item value was below 0.3, then there were 10 question items left that had a high level of reliability.